Metodologias ativas de aprendizagem e novas tecnologias digitais: um olhar sobre o professor da era digital no curso de Administração em Uberlândia - MG - Araujo, Leandro Luiz de (2020)
The present scientific investigation, linked to the research line Media, Education and Communication (MEC) of the Postgraduate Program in Technologies, Communication and Education (PPGCE) of the Faculty of Education (FACED) of the Federal University of Uberlândia (UFU), presents a cut between the educational process and its relationship with active learning methodologies and new digital technologies. The main objective is to know and describe the teaching knowledge of teachers trained and working in higher education courses, on-site, from two educational institutions , being a public and a private one, from the city of Uberlândia / MG, facing the active learning methodologies and new digital technologies applied by them in their classes. In addition, the specific objectives are in line with existing approaches between active learning methodologies with digital technologies and the proposed elaboration of an educational product that provides an online meeting point for relevant information on the subject. For its realization, a scientific investigation, initiates the theoretical dialogue by deepening conceptually, through bibliographical and documentary research, the ideals of FREIRE (1996), MORAN (2007), MORAN; MASETTO; BEHRENS (2010), LAVAL (2004), SODRÉ (2012), ANTUNES; PINTO (2017), KENSKI (2012), GÓMEZ (2015), CAMARGO; DAROS (2018), BACICH; MORAN (2018) and other authors, who are dedicated to the impacts on the educational process of technological, economic and social evolution. In this way, the investigation continues with the collection of data through questionnaires structured in the qualitative and quantitative approach, divided into two large blocks, the first corresponding to the active methodologies and the new technologies and the second referring to the teaching profile. Subsequently, the results obtained in the field are tabulated and promoted, showing the contrasts between the theory and practice of the research participants. Finally, an investigation presents a proposal for an educational product that provides a point for an online meeting of relevant information on this topic.